Periodic solutions of systems of differential equations with random right-hand sides - Danilov, V. Ya.; Martynyuk, D. I.; Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove a theorem on the existence of periodic solutions of a system of differential equations with random right-hand sides and small parameter of the form dx/dt=εX(t, x, ξ(t)) in a neighborhood of the equilibrium state of the averaged deterministic system dx/dt=εX 0(t).